2016
DOI: 10.1002/art.39629
|View full text |Cite
|
Sign up to set email alerts
|

Association of Increased Treg Cell Levels With Elevated Indoleamine 2,3‐Dioxygenase Activity and an Imbalanced Kynurenine Pathway in Interferon‐Positive Primary Sjögren's Syndrome

Abstract: Objective. Indoleamine 2,3-dioxygenase (IDO), the rate-limiting enzyme that converts tryptophan to kynurenine, is driven in part by type I and type II interferons (IFNs). Naive T cells are polarized into FoxP31 Treg cells upon exposure to either IDO1 cells or kynurenine. Recent studies have suggested that the kynurenine pathway reflects a crucial interface between the immune and nervous system. The aims of the present study were to evaluate whether Treg cell levels are elevated, in conjunction with increased I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 51 publications
(88 reference statements)
1
46
0
Order By: Relevance
“…(II) Monocytes with high MDA5 protein expression showed clear nuclear expression of pIRF7, indicating TLR pathway activation combined with MDA5 expression in IFNpos patients with pSS. Although only a limited number of biopsies were studied here we observed TLR7, RIG-I and MDA5 expression, in concurrence with high MxA expression2 3 35 in SG infiltrates indicating that in addition to a possible role in systemic activation of IFN type I, these molecules could also contribute to local IFN activation in pSS SGs. (III) IFNpos pSS monocytes express the RLR-downstream signalling molecule TBK1 at an increased level compared with IFNneg patients.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…(II) Monocytes with high MDA5 protein expression showed clear nuclear expression of pIRF7, indicating TLR pathway activation combined with MDA5 expression in IFNpos patients with pSS. Although only a limited number of biopsies were studied here we observed TLR7, RIG-I and MDA5 expression, in concurrence with high MxA expression2 3 35 in SG infiltrates indicating that in addition to a possible role in systemic activation of IFN type I, these molecules could also contribute to local IFN activation in pSS SGs. (III) IFNpos pSS monocytes express the RLR-downstream signalling molecule TBK1 at an increased level compared with IFNneg patients.…”
Section: Discussionsupporting
confidence: 61%
“…This imbalanced profile possibly prevents IFN overactivation and its potential downstream consequences for autoantibody production and systemic manifestations, coinciding with a particular disease phenotype different from that of IFNpos pSS 46. A tightly regulated balance of these RNA-sensing receptor systems seems essential for tolerance preservation35 and preventing the onset of systemic autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown an elevation in TNF-α levels in salivary glands and sera of SS patients 21–24 . We further showed in this study that salivary gland TNF-α expression increases with age in NOD mice accompanying the SS development, supporting a possible pathogenic role of this cytokine in SS, especially in the stage prior to the disease onset at 10 weeks of age.…”
Section: Discussionmentioning
confidence: 90%
“…TNF-α promotes the pathogenesis of these disorders by promoting production of pro-inflammatory cytokines, recruitment of immune and inflammatory cells to local tissues and destruction of organs 18, 20 . In SS patients, elevated TNF-α expression in both salivary gland and serum has been described compared to non-SS sicca patients 21–24 . TNF-α can be produced by many cell types, including salivary gland epithelium and salivary gland-infiltrating T helper 1 and T cytotoxic 1 cells 10, 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Another study has shown an association between higher plasma kynurenine levels and immunosuppression due to loss of CD4 + and CD8 + T cells during sepsis (Darcy et al, 2011). An association between increased Tregs, elevated IDO activity, and imbalanced kynurenine pathway is observed in interferon-positive primary Sjögren's syndrome (PSS) (Maria et al, 2016). Thus it will be interesting to observe the impact of kynurenine levels on Tregs in sepsis and impact of IDO inhibition during sepsis.…”
Section: Immunometabolic Control Of Tregs Function During Sepsismentioning
confidence: 99%